Proceedings of the 3rd Czech-China Scientific Conference 2017 - Gottvald, Jaromir; Praus, Petr (IntechOpen, 2017)
This book comprises the proceedings of the 3rd Czech-China Scientific Conference 2017 which was held on 7th June 2017 in Ostrava, Czech Republic. The objective of the conference was to present the latest achievements in the fields of advanced science and technology that stem from research activities of VŠB - Technical University of Ostrava and its Chinese partners. The conference was multi-topical, enabling young researchers from different scientific areas to present their findings and experience atmosphere of an international conference. The conference attracted specialists from the areas of economy, safety in civil engineering and industry, materials technologies, environment, and computational science.